PENGARUH DIREKSI PEREMPUAN PADA PERFORMA BANK DI ASIA TENGGARA - Oktaviani, Ayu; Nor Hikmah; Novika Rosari; Wahyu; Hamdani (JWM (JURNAL WAWASAN MANAJEMEN), 2024)
This study aims to find out the impact of the women's directory on the performance of financial companies imitating the Tobin's Q ratio. This research uses the Weighted Least Square method with the IBM SPSS application. Data collection techniques using the documentation method. The data in this study consisted of secondary data taken from the Indonesia Stock Exchange or related company websites (the number of samples in this study were 49 companies spread across Southeast Asia from 2017 - 2020). The results of this study indicate that the variables of female directors, profitability and company size have no effect on the company's financial performance, while the leverage variable has a significant positive effect on the company's financial performance.